2014
DOI: 10.1074/jbc.m113.543389
|View full text |Cite
|
Sign up to set email alerts
|

A KcsA/MloK1 Chimeric Ion Channel Has Lipid-dependent Ligand-binding Energetics

Abstract: Background:The mechanism of ligand gating in physiologically important cyclic nucleotide-modulated channels is unknown. Results: We constructed and purified a chimeric ion channel with activity modulated by cAMP and used it to measure ligand-binding energetics. Conclusion: cAMP binds with high lipid-dependent affinity to the chimeric channel. Significance: The availability of a good protein preparation enables assays that shed light on ligand gating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Here we elucidated the mechanism of Ca 2+ dependent gating in MthK, a prokaryotic BK channel homologue with a conserved Ca 2+ -dependent gating ring but devoid of voltage-sensing domains 5 , thus allowing unhampered study of the Ca 2+ -dependent gate. Using a flux assay with high time resolution 38 39 , we were able to characterize the closed-state block of MthK by QA blockers ( Fig. 1 ), and find that Ca 2+ induces changes at the intracellular channel entryway, which controls K + conductance via a gate at the selectivity filter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we elucidated the mechanism of Ca 2+ dependent gating in MthK, a prokaryotic BK channel homologue with a conserved Ca 2+ -dependent gating ring but devoid of voltage-sensing domains 5 , thus allowing unhampered study of the Ca 2+ -dependent gate. Using a flux assay with high time resolution 38 39 , we were able to characterize the closed-state block of MthK by QA blockers ( Fig. 1 ), and find that Ca 2+ induces changes at the intracellular channel entryway, which controls K + conductance via a gate at the selectivity filter.…”
Section: Discussionmentioning
confidence: 99%
“…We show that Ca 2+ -dependent gating occurs at the selectivity filter, and not at the bundle crossing, by detecting closed-channel block by large QA molecules that bind immediately below the selectivity filter. By utilizing a stopped-flow-based flux assay 38 39 , Ca 2+ and blocker are very quickly applied to MthK liposomes with the time resolution essential for discriminating between gate locations. Tetrapentylammonium (TPeA) binds ∼100-fold slower to the closed state than to the open state, indicating a significant conformational change during closing that reduces but does not eliminate blocker access.…”
mentioning
confidence: 99%
“…The use of amphipols to stabilize MPs has recently led to a high-resolution de novo structure determination of a cation channel at a resolution of 3.4 Å (41), breaking the sidechain resolution barrier. Together with promising studies using scaffold-protein nanodiscs (42,43), as well as initial studies with native nanodiscs (44), these new developments suggest that native nanodiscs may become a powerful alternative to enable high-resolution structural characterization of MPs in their native environment.…”
Section: Discussionmentioning
confidence: 99%
“…This type of constructs is a great complimentary of existing methods, and has the advantages of 1) stabilizing a variety of IMPs in their native conformation in a detergent-free environment, 2) presenting accessibility of both intra-and extra-cellular domains of the target IMP to ligand/ effector proteins, and 3) generating a solution with homogenous particle size. Although many different types of IMPs have been successfully incorporated in Nanodiscs, examples of the assembly of ion channel Nanodiscs are limited [20,21]. Recent study on KcsA/MloK1 [21] demonstrated benefit of using Nanodisc to determine ligand binding to grafted cyclic nucleotide binding domain (CNBD) from MloK1 onto KcsA in a detergent free environment.…”
Section: Introductionmentioning
confidence: 98%
“…Although many different types of IMPs have been successfully incorporated in Nanodiscs, examples of the assembly of ion channel Nanodiscs are limited [20,21]. Recent study on KcsA/MloK1 [21] demonstrated benefit of using Nanodisc to determine ligand binding to grafted cyclic nucleotide binding domain (CNBD) from MloK1 onto KcsA in a detergent free environment. However, details of conformation and inhibitor binding properties in the pore region of the potassium channel remained unclear.…”
Section: Introductionmentioning
confidence: 98%